2021
DOI: 10.1002/alr.22771
|View full text |Cite
|
Sign up to set email alerts
|

Association of a standardized measure of nasopharyngeal inflammation with Eustachian tube dysfunction questionnaire score

Abstract: Background: Standardized diagnostic criteria for Eustachian tube (ET) dysfunction (ETD) have not been established. The purpose of this study was to characterize the relationship between ET inflammation and ETD symptoms and to determine the diagnostic performance of a quantitative score. Methods: Patients were enrolled in a rhinology clinic between October 2018 and June 2019. Patients underwent nasal endoscopy and completed the 7-item Eustachian Tube Dysfunction Questionnaire (ETDQ-7). Nasopharyngeal inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…The results of this preliminary study may lead to the development of new basic science studies investigating the potential toxicity of elastase on mucosa cells of the upper aerodigestive tract. Such research may be useful for many otolaryngological conditions where LPR is involved, including vocal fold benign lesions, 29 chronic pharyngitis, 30 chronic rhinosinusitis, 31 otitis media, 32 Eustachian tube dysfunction, 33 or primary burning mouth syndrome 34 …”
Section: Discussionmentioning
confidence: 99%
“…The results of this preliminary study may lead to the development of new basic science studies investigating the potential toxicity of elastase on mucosa cells of the upper aerodigestive tract. Such research may be useful for many otolaryngological conditions where LPR is involved, including vocal fold benign lesions, 29 chronic pharyngitis, 30 chronic rhinosinusitis, 31 otitis media, 32 Eustachian tube dysfunction, 33 or primary burning mouth syndrome 34 …”
Section: Discussionmentioning
confidence: 99%
“…Pan et al 49 evaluated change in nasalance scores in patients with CRS using oral passage, mixed passage, and nasal sentences and demonstrated that patients with severe disease and higher polyp grade had lower nasalance scores. Bergeron et al 50 demonstrated an association between inflammatory findings at the nasopharyngeal Eustachian tube orifice and clinically significant Eustachian tube dysfunction symptoms.…”
Section: Novel Technologies and Outcome Measuresmentioning
confidence: 99%